2009
DOI: 10.4315/0362-028x-72.8.1735
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Chitosan against Campylobacter spp. and Other Microorganisms and Its Mechanism of Action

Abstract: The antimicrobial activities of three chitosans with different molecular masses against six gram-negative and three gram-positive bacteria were examined. Campylobacter spp. were the microorganisms most sensitive to chitosan, regardless of their molecular mass. The MIC of chitosan for Campylobacter ranged from 0.005 to 0.05%, demonstrating the global sensitivity of campylobacters to chitosan. Chitosan caused a loss in the membrane integrity of Campylobacter, measured as an increase in cell fluorescence due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 18 publications
0
29
0
1
Order By: Relevance
“…For all these reasons, new potential antibacterial compounds for controlling Campylobacter are necessary. In a recent work, we demonstrate the sensitivity of Campylobacters to chitosans within a range of MW from 643 to 120 kDa (Ganan, Carrascosa, & Martínez-Rodríguez, 2009). However, the antimicrobial capacity of chitosan oligosaccharides on C. jejuni is unknown.…”
Section: Introductionmentioning
confidence: 87%
“…For all these reasons, new potential antibacterial compounds for controlling Campylobacter are necessary. In a recent work, we demonstrate the sensitivity of Campylobacters to chitosans within a range of MW from 643 to 120 kDa (Ganan, Carrascosa, & Martínez-Rodríguez, 2009). However, the antimicrobial capacity of chitosan oligosaccharides on C. jejuni is unknown.…”
Section: Introductionmentioning
confidence: 87%
“…Thus, it has been proposed that the positively charged amino groups of the glucosamine units interact with negatively charged components in microbial cell membranes, altering their barrier properties, and thereby preventing the entry of nutrients or causing the leakage of intracellular contents [95][96][97][98][99][100]. Another reported mechanism involves the penetration of low-molecular weight chitosan into the cell, binding to DNA and the subsequent inhibition of RNA and protein synthesis [101].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Chitosan is a molecule that has antimicrobial activity against many Gram-negative and Gram-positive bacteria (Rabea et al, 2003;Zheng and Zhu, 2003;Ganan et al, 2009;Friedman and Juneja, 2010;Batista et al, 2011;Islam et al, 2011). For example, Lee et al (2009) demonstrated both in vitro and in vivo (mice) that chitosan oligosaccharides have antibacterial effect on the Gram-negative bacterium Vibrio vulnificus, which causes sepsis and gastrointestinal illness in humans.…”
Section: Resultsmentioning
confidence: 99%